2007
DOI: 10.1242/jcs.010876
|View full text |Cite
|
Sign up to set email alerts
|

PTEN plays a role in the suppression of lateral pseudopod formation duringDictyosteliummotility and chemotaxis

Abstract: It has been suggested that the phosphatydylinositol (3,4,5)-trisphosphate [PtdIns(3,4,5)P3] phosphatase and tensin homolog PTEN plays a fundamental role in Dictyostelium discoideum chemotaxis. To identify that role, the behavior of a pten– mutant was quantitatively analyzed using two-dimensional and three-dimensional computer-assisted methods. pten– cells were capable of polarizing and translocating in the absence of attractant, and sensing and responding to spatial gradients, temporal gradients and natural wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(123 citation statements)
references
References 94 publications
(165 reference statements)
10
113
0
Order By: Relevance
“…pten-/-cells express defects in motility and form pseudopodia at random locations (Wessels et al, 2007). PTEN localisation in our experiments was done in the same way as for PI3kinase, and the results show that under nutrient rich conditions PTEN molecules were localised in the endosomal vesicles (Fig.…”
Section: Spatial Differences Of Signalling Molecules Within Motile Cellsmentioning
confidence: 78%
See 1 more Smart Citation
“…pten-/-cells express defects in motility and form pseudopodia at random locations (Wessels et al, 2007). PTEN localisation in our experiments was done in the same way as for PI3kinase, and the results show that under nutrient rich conditions PTEN molecules were localised in the endosomal vesicles (Fig.…”
Section: Spatial Differences Of Signalling Molecules Within Motile Cellsmentioning
confidence: 78%
“…On the other hand during early starvation, intense PTEN staining could be seen in the cytoplasm and at the posterior pseudopods and there was no vesicularisation of fluorescence, implying that starvation of cells initiated recycling of PTEN from the cytoplasm to the lateral membrane. According to earlier reports, in motile chemotaxing cells much of the PTEN delocalises from the leading edge and it gets distributed mostly on the lateral membranes (Funamoto et al, 2002;Wessels et al, 2007). The functional consequence of this in the starved cells could be dephosphorylation of PIP3 (leading to the formation of PIP2) and turnover of focal adhesions required for the rapid movement of the cell.…”
Section: Spatial Differences Of Signalling Molecules Within Motile Cellsmentioning
confidence: 94%
“…Dictyostelium cells achieve chemotaxis by biasing decisions between randomly generated pseudopodia (Andrew and Insall, 2007;Varnum-Finney et al, 1987). PI3K probably controls the rate at which pseudopodia are randomly generated, but not the direction of pseudopod formation, whereas PTEN suppresses lateral pseudopod formation, keeping cells on track (Wessels et al, 2007). In Dictyostelium, PI3K, PTEN and polarized PtdIns(3,4,5)P 3 are thus mainly involved in the control of cell speed and pseudopod formation.…”
Section: Chemotaxis In the Absence Of Pi3k And/or Ptenmentioning
confidence: 99%
“…Initial experiments in Dictyostelium suggested that the activity of PI3K and PTEN, and the subsequent formation of localized intracellular PtdIns(3,4,5)P 3 gradients, are required for chemotaxis, especially for external-gradient sensing during chemotaxis (Funamoto et al, 2001;Huang et al, 2003;Iijima and Devreotes, 2002). However, studies over the past year indicate that PI3K and PTEN activity and localized PtdIns(3,4,5)P 3 gradients, although important, are dispensable for chemotaxis under many conditions (Andrew and Insall, 2007;Hoeller and Kay, 2007;Loovers et al, 2006;Takeda et al, 2007;Van Haastert and Veltman, 2007;Wessels et al, 2007). Here, we first discuss the importance of PI3K, PTEN and PtdIns(3,4,5)P 3 for cell motility and cytoskeletal regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, some proteins can relocalize during cell migration, such as PTEN dissociating along the leading edge and accumulating at the cell rear during chemotaxis (14,31). We studied the cellular distribution of LPA 2 during chemotaxis by transiently overexpressing an EGFP-tagged LPA 2 ( Fig.…”
Section: Lpa Gradient Induces a Spatially Restricted Reduction In Thementioning
confidence: 99%